Pemanfaatan Gedebok Pisang Fermentasi Sebagai Pakan Alternatif Ternak Sapi Di Desa Kali Bening Kecamatan Tugumulyo Kabupaten Musi Rawas - Betty Herlina; Ririn Novita; Natasya Aditya Putri (Gayaku Publisher, 2022)
The purpose of this activity is to reduce the presence of banana gedebog waste in the Kali Bening Village area by utilising fermented banana gedebog as an alternative feed for cattle and to increase the knowledge of the Kali Bening Village community about fermented feed from banana gedebog. The implementation method is to socialise the importance of alternative feed made from banana gedebok for livestock in Kali Bening Village. This community service activity was carried out smoothly, and the breeders were very enthusiastic about participating in the activity so that breeders could increase their knowledge of utilising banana kedebog waste as alternative feed for cattle